Proceedings of the 2012 (3rd) International Conference on Engineering, Project, and Production Management 2012
DOI: 10.32738/ceppm.201209.0010
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Relationships between Employees’ Safety and Productivity

Abstract: Safety culture is the product of individual and group values, attitudes, perceptions, competencies, and patterns of behavior that determine the commitment to and organization's health and safety management. It varies from one country to another. Employees may behave differently due to their background differences in race, nation, religion, and community. To achieve a positive safety culture, employee involvement and satisfaction must be considered, as it drives continuous improvement, which may lead to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…GFI and AGFI should be 0.9 or more (Awang, 2012;Hooper et al, 2008), though value of 0.80 is acceptable (Chin and Todd, 1995 as cited in Rivers et al, 2013). CFI should be more than 0.9 (Hooper et al, 2008), though 0.80 or more represent a good fit (Browne and Cudeck, 1993; as cited in Chinda et al, 2012).…”
Section: Model Fitmentioning
confidence: 99%
“…GFI and AGFI should be 0.9 or more (Awang, 2012;Hooper et al, 2008), though value of 0.80 is acceptable (Chin and Todd, 1995 as cited in Rivers et al, 2013). CFI should be more than 0.9 (Hooper et al, 2008), though 0.80 or more represent a good fit (Browne and Cudeck, 1993; as cited in Chinda et al, 2012).…”
Section: Model Fitmentioning
confidence: 99%
“…As can be seen in Table 4, all the fit indices measured according to the suggestions (Hu & Bentler, 1999; Schreiber et al, 2006) are in a good and desirable condition which indicates a good fit of the variables with the data. But IFI and CFI indices showed a slightly lower than other indices, but they are in an acceptable range (Browne & Cudeck, 1992; Chinda et al, 2012; Okada et al, 2020). In general, it can be concluded that the data have an acceptable fit with the variables examined in this study and the accuracy of the study's measurement model can be ensured.…”
Section: Resultsmentioning
confidence: 97%
“…Terdapat pengaruh signifikan dari jaminan keselamatan dan kesehatan terhadap produktivitas kerja. Sesuai hasil temuan penelitian terdahulu dari Shikdar & Sawaqed (2003); Katsuro et al (2010); Chinda et al (2012) sesuai dengan hasil penelitian ini. Ini dapat dipahami bahwa praktik K3 yang baik tidak hanya mengurangi risiko fisik dan psikologis, tetapi juga meningkatkan efisiensi dan kinerja keseluruhan.…”
Section: Jaminan Keselamatan Dan Kesehatan Terhadap Produktivitas Kerjaunclassified